Influence of coal heat treatment parameters on physical-chemical properties of smokeless fuel - Kim, S.V.; Kim, V.A.; Sariev, O.R.; Kudarinov, S.Kh.; Bogoyavlenskaya, O.A.; Orlov, A.S.; Orlova, V.V.; Zhdanov, A.V. (KSU Publ., 2018)
A series of experiments on coking long-flame coals by high-speed thermooxidative pyrolysis was carried out as a part of smokeless fuel technology development from domestic energy coals. The objective of experiments was to determine the influence of basic technological parameters of the coking process (heating rate, coking temperature) on the final physical-chemical properties of the semi-coke, which is an initial material for briquetted smokeless fuel manufacture. The experiments were carried out in a Tamman resistance furnace at 600–1100 ºC imitating the coking process in industrial shaft furnace. The rate of heating and the final temperature of coking were found the most important control factors ensuring the production of lump coke with sufficient strength. In the mentioned temperature interval, the reactivity of semi-coke changes by a complicated pattern varying from 3.5 to 9.7 ml/g·s. Along with coking temperature and heating rate, the structural strength of semi-coke grows monotonically, reaching 80 % at heating rate of 90 degrees per minute and a temperature of 1100 ºC. Thus, the results of this work allow us to conclude that the most rational temperature range for smokeless fuel production by means of high-speed pyrolysis of young high-volatile coal is found within 600–700 ºC (the temperature interval of semi-coking). To ensure sufficient structural strength of semicoke the rate of coal heating should be at least 30 ºC/min. A highly active material with a reactivity of over 9 ml/g·s and a sufficiently high strength and a residual volatiles content of about 8–11 % can be obtained using this method.
Көмірді термиялық өңдеу режимдерінің түтінсіз отынның физика-химиялық қасиеттеріне əсерін зерттеу
Влияние режимов термообработки угля на физико-химические свойства бездымного топлива
Keywords: smokeless fuel; thermo-oxidative pyrolysis; energy coals; semi-coke; coking temperature; structural strength; reactivity; volatile substances